Return to Smith? Harper-Era Mandatory Minimum Sentences in Canadian Courts (2008–2023) - Dell, Brendan (Ottawa Law Review / Revue de droit d’Ottawa, 2023)
Following the Supreme Court of Canada’s decision in R v Smith (1987), which struck down a mandatory minimum sentence (MMS) for drug trafficking, it took nearly three decades before the Court would nullify another MMS. This 28-year span saw the Court exhibit judicial restraint and deference to the government regarding the constitutionality of MMS. However, in 2015, the Court invalidated an MMS enacted by the Harper government in R v Nur. The MMS in Nur was one of over 40 MMS provisions introduced by the Harper government between 2006 and 2015.As sentencing policy engages Parliament’s exclusive jurisdiction to legislate criminal law, judicial discretion in sentencing, and section 12 of the Charter, these Harper-era sentencing provisions provide a unique opportunity to study the institutional roles in sentencing and the constitutionality of such provisions.This article offers a comprehensive overview of the MMS enacted by the Harper government and examines how these provisions have been treated by Canadian courts, particularly focusing on the constitutional test for section 12 of the Charter. By analyzing appellate-level and Supreme Court cases featuring Charter challenges to Harper-era MMS, the article found that these provisions are being struck down at a high rate (76%). The findings indicate a loosening of judicial restraint and deference to government in this area and highlight significant issues with the reasonable hypothetical aspect of the section 12 test. Ultimately, the article argues for a better understanding of the complementary roles of the legislature and judiciary in sentencing.